The German Government’s Effort to Stabilize Human Security Due to The Refugee Crisis from Syria 2017-2020 - Balqis, Nurliya; Susilowati, Ida; Chandra, Rudi (SALAM: Jurnal Sosial dan Budaya Syar-i, 2024)
In 2011, the armed conflict in Syria triggered a massive wave of refugees to various countries, especially in Europe. Germany became one of the main destinations for refugees due to its open policy towards asylum seekers. However, the economic crisis that hit Europe in 2013 caused major challenges in accepting and managing refugees. This research aims to analyse the impact of the Syrian refugee crisis on refugee policy and security stability in Germany. This research uses a qualitative method with a descriptive analysis approach and human security theory as the main foundation. Data analysis techniques include collecting, reducing, processing, presenting, and drawing conclusions based on secondary sources such as academic journals, scientific articles, international organisation reports, and German government policy documents. The research shows that the surge of Syrian refugees has had a significant impact on various aspects of Germany, especially in the security, economic, and social fields. To address the problem, the German government implemented various policies, including the establishment of state agencies such as BAMF, BKA, and BFV that are responsible for refugee administration, security, and prevention of radicalisation. In addition, cooperation with social organisations such as Caritas Germany and coordination with UNHCR are also carried out to ensure the welfare of refugees and maintain the stability of the country. Thus, the Syrian refugee crisis not only affects Germany domestically, but also influences European refugee policy more broadly. This research provides insight into how refugee surges due to armed conflict can affect the political, economic, and social stability of a receiving country.Keywords: Refugee Crisis, Human Security, Migration Policy, Germany, Syria